DINO +: DIGITAL GAME FOR PEOPLE WITH ASD - dos Santos, Luiz Cláudio Machado; dos Santos, Maria Adélia Icó M.; Rios, Jocelma Almeida; Winkler, Ingrid; dos Santos, Luis Felipe Coelho Carvalho; Borges, Adrian Willy da Silva (Seven Editora, 2026)
This article discusses the development of a digital game aimed at children with ASD. Digital games are a strategy used in various activities to support the learning process of these children, serving as a link with a multidisciplinary and interdisciplinary team. This article focuses on developing an educational game accessible to people with autism. The objective of this article is to develop a game in Unity by integrating scriptwriting, visual art, and sound composition through programming, addressing autism, and making it usable by teachers, children, and those interested in the subject. The methodological process of this article is based on a literature review, providing a rich and well-founded reference to contribute to the game’s development.Finally, a free game is presented in both desktop and web versions, along with a mobile version for Android, available on the mentioned platforms and accessible to any user. DOI: https://doi.org/10.56238/sevened2026.008-013